Recent Development of Fibrous Hydrogels: Properties, Applications and Perspectives - Wen Luo; Liujiao Ren; Bin Hu; Huali Zhang; Zhe Yang; Lin Jin; Di Zhang (Advanced Science)
Abstract Fibrous hydrogels (FGs), characterized by a 3D network structure made from prefabricated fibers, fibrils and polymeric materials, have emerged as significant materials in numerous fields. However, the challenge of balancing mechanical properties and functions hinders their further development. This article reviews the main advantages of FGs, including enhanced mechanical properties, high conductivity, high antimicrobial and anti‐inflammatory properties, stimulus responsiveness, and an extracellular matrix (ECM)‐like structure. It also discusses the influence of assembly methods, such as fiber cross‐linking, interfacial treatments of fibers with hydrogel matrices, and supramolecular assembly, on the diverse functionalities of FGs. Furthermore, the mechanisms for improving the performance of the above five aspects are discussed, such as creating ion carrier channels for conductivity, in situ gelation of drugs to enhance antibacterial and anti‐inflammatory properties, and entanglement and hydrophobic interactions between fibers, resulting in ECM‐like structured FGs. In addition, this review addresses the application of FGs in sensors, dressings, and tissue scaffolds based on the synergistic effects of optimizing the performance. Finally, challenges and future applications of FGs are discussed, providing a theoretical foundation and new insights for the design and application of cutting‐edge FGs.